The Use of Vasopressor Agents in Free Tissue Transfer for Head and Neck Reconstruction: Current Trends and Review of the Literature - Akash N. Naik; Taylor Freeman; Michael M. Li; Scarlett Marshall; Akina Tamaki; Enver Ozer; Amit Agrawal; Stephen Y. Kang; Matthew O. Old; Nolan B. Seim (Frontiers Media S.A., 2020)
Background/ObjectivesMicrovascular free tissue transfer has become essential to head and neck reconstruction and recent advancements in microvascular surgery have led to excellent surgical outcomes. However, there continues to be controversy and a stigma associated with the use of perioperative intravenous vasopressor agents among both surgeons and anesthesiologists. Due to concern for vasoconstriction of peripheral vasculature flowing to the denervated tissue flap, there remains concerns about potential thrombosis, decreased tissue perfusion and ultimately flap failure. This topic becomes even more important as vasopressors play an essential role in new Extended Recovery After Surgery (ERAS) protocols being put in place to optimize postoperative recovery for patients. The purpose of this study was to comprehensively review the role and safety as well as discuss current trends with intraoperative vasopressor agents in free tissue transfer for head and neck reconstruction.MethodsA scoping literature review was conducted of all studies that examined the use of vasopressor agents during head and neck free flap tissue transfer. Primary and secondary outcomes included free flap survival, arterial thrombosis, venous congestion, need for revision surgery, and other postoperative complications.ResultsOne prospective and nine retrospective studies were identified. Phenylephrine and ephedrine were the most common vasopressors reported; the rate of vasopressor use ranged from 53% to 85% and administration methods included both bolus and infusion. The included studies did not show any significant association between the use of vasopressors and free flap failure, pedicle thrombosis, or other flap complications.ConclusionThe administration of vasopressors during microvascular free tissue transfer for head and neck reconstruction does not seem to be associated with increased flap failure rates or other postoperative morbidities. Moreover, vasopressors may provide overall improved hemodynamic stability and help to limit overall fluid administration and subsequent postoperative complications. Additional prospective investigation is warranted to further elucidate and establish evidence-based recommendations regarding the type, timing, and dose of vasopressors to further enhance free flap survival and patient outcomes.